Vertebrate fauna at the Allosaurus fossil-site of Andrés (Upper Jurassic), Pombal, Portugal - Malafaia, E.; Ortega, F.; Escaso, F.; Dantas, P.; Pimentel, N.; Gasulla, J. M.; Ribeiro, B.; Barriga, F.; Sanz, J. L. (Journal of Iberian Geology, 2010)
An overview of the faunistic diversity of the Andres fossil-site from the Portuguese Upper Jurassic is presented. This work provides a preliminary approach on the vertebrate fauna known at present. Although this quarry is known since the 1990’s, due to the description on the first robust evidence of a member of the neotetanuran genus Allosaurus outside North America, the results presented here are mainly derived from the analysis of the elements found during the second and third field seasons in 2005. At the moment, among the material collected from Andrés it was identified remains that represent a diverse vertebrate fauna, including fishes, sphenodonts, crocodrylomorphs, pterosaurs, and at least, seven distinct dinosaur forms. The recovery of this diverse and abundant osteological collection from one unique fossil-site is noteworthy for the Upper Jurassic Portuguese record, and only comparable with those from the Guimarota coalmine. Due to these two features plus the good preservation of the fossils, the Andres quarry may be a site of reference for the analysis of vertebrate ecosystems from the Portuguese Upper Jurassic. Dinosaur elements are the most abundant fossils, and among them it is particulary common the presence of remains identified as Allosaurus. These new evidences allow testing the previus phylogenetical hypothesys ascribing the firsts theropod remains from Andrés to A. fragilis, a species described in synchronic levels of the North American Morrison Formation. The similarity between the Allosaurus remains collected in Andres and some specimens from the Morrison Formation seems to point the existence of a genetic flow between some continental vertebrates on both sides of the proto-north Atlantic during the Upper Jurassic. Favourable tectonic conditions for the occurrence of punctual contacts between the two continents is, at present, the best scenario for explain this situation.